2014
DOI: 10.3109/1547691x.2014.902877
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative induction of pro-inflammatory cytokine formation by human monocyte-derived macrophages following exposure to manganesein vitro

Abstract: Manganese (as Mn(2+)), a superoxide dismutase mimetic, catalyzes the formation of the relatively stable membrane-permeable reactive oxygen species (ROS) hydrogen peroxide (H2O2), a mediator of intracellular redox signaling in immune and inflammatory cells. The goal of this study was to investigate the potential for Mn(2+), via its pro-oxidative properties, to activate production of pro-inflammatory cytokines/chemokines IL-1β, IL-6, IL-8, IFNγ, TNFα, and G-CSF by human monocyte-derived macrophages in vitro. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Cytokines have been increasingly implicated in acute and chronic neuronal degeneration [45]. Recent clinical studies have reported increased levels of TNF-, IL-6, IL-1b, and interferon- in post-mortem brain tissues [46,47]. In our study, we observed strong relationships between the levels of Mn and of the pro-infl ammatory cytokines IL-6 and TNF-, as well as the adhesion marker sE-selectin.…”
Section: Discussionsupporting
confidence: 66%
“…Cytokines have been increasingly implicated in acute and chronic neuronal degeneration [45]. Recent clinical studies have reported increased levels of TNF-, IL-6, IL-1b, and interferon- in post-mortem brain tissues [46,47]. In our study, we observed strong relationships between the levels of Mn and of the pro-infl ammatory cytokines IL-6 and TNF-, as well as the adhesion marker sE-selectin.…”
Section: Discussionsupporting
confidence: 66%
“…To determine if the decrease in M1 polarization as measured by cell surface and gene expression changes its function, we used carboxy‐H2CDFDA to detect ROS production via flow cytometry as macrophages produce ROS in order to neutralize pathogens (Mokgobu et al ., ). Stimulating macrophages towards an M1 phenotype with LPS + IFN‐γ demonstrated a greater capacity to produce ROS compared with basal levels observed in M0 macrophages.…”
Section: Resultsmentioning
confidence: 97%
“…Asides from examining M1 phenotype using cell surface markers and gene expression of M1‐associated cytokines, the effect of HDL on the functional capacity of LPS + IFN‐γ‐induced M1 macrophages was examined. Our data confirms an increase in ROS generation in M1 macrophages (Mokgobu et al ., ) where it is likely to trigger activation of the NFκB pathway, and in turn increase inflammatory cytokines expression (Fenyo and Gafencu, ). Furthermore, in the setting of atherosclerosis, oxidative modification of LDLs induced by ROS results in an increase in foam cell formation (Yla‐Herttuala, ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS could also directly induce inflammatory cytokine expression/production via regulation of immune signaling through TLR4-mediated NF-κB activation [28]. It was reported that the Mn 2+ -mediated induction of inflammatory cytokine production was associated with increased production of H 2 O 2 , and effectively attenuated by the H 2 O 2 - scavenger dithiothreitol, and partially prevented by inhibitors of NF-κB and p38MAP kinase [43]. ROS has been shown to induce gene expression of inflammatory mediators, such as IL-1 and TNF-a [44].…”
Section: Discussionmentioning
confidence: 99%